Commuting, Residence and Workplace Location Attractiveness and Local Public Goods - Klaus Nowotny (Austrian Institute of Economic Research (WIFO), 2010)
Being at the heart of today's working life, commuting is of central interest to geographers, policy makers, transport planners and economists alike. This article analyses aggregate commuting using various groups of variables. A special focus is on the questions whether and how the provision of local public goods, such as educational institutions or health care facilities, and local amenities affect commuting decisions on the aggregate level and to what extent commuting can be explained by labour market characteristics at the source and target units. The empirical investigation analyses aggregate commuting flows between municipalities of an Austrian province using censored regression and count data models.
Keywords: 330; commuting; gravity model; censored regression; Pendelverkehr; Lokale öffentliche Güter; Arbeitsplatz; Wohnstandort; Gravitationsmodell; Österreich